A retrospective study of paradigm and outcome of acute poisoning cases in a tertiary care teaching hospital in Southern India - C., Arulmurugan; Ahmed, Sarfaraz; Gani, Mohammad (International Journal of Research in Medical Sciences, 2017)
Background: Acute poisoning is a medical emergency. It is important to know the nature, outcome and severity of acute poisoning cases in order to make appropriate prevention and treatment. This study is conducted to assess the paradigm and outcome of acute poisoning cases in a tertiary care hospital in Tamilnadu. Methods: This is a retrospective study conducted in a tertiary care hospital in Tamilnadu. The study included 169 cases and data regarding age, sex, time elapsed after intake, name of the poisons, chemical type; duration of hospital stay; outcome and severity were collected in the structured proforma. Results: Incidence was high among males (60.36%) compared to females (39.64%). Most of the cases of acute poisoning were in the age group 10 to 30 years (60.95%) followed by 30 to 50 years age group (30.77%). A majority of poisoning cases (27.2%) were due to organophosphorus (OPC) insecticide. Total mortality was found to be 5.32%. Mortality rate due to Paraquat, Abrus Pretorius seeds was significantly high compared with OPC because there is no specific antidote. Time lapse had a very significant role in the mortality in cases of poisoning. Conclusions: Poisoning is common with young males. The mortality is high, in cases of self-poisoning with parquet and abrus seeds. Despite the highest consumption rate, no mortality was observed with organophosphorus because of early medical intervention and specific antidote. Early medical care in a tertiary care hospital will help to reduce significant mortality in India.